Recent population changes in British ducks, 1948 to 1960 - Eltringham, S K; Atkinson-Willes, G L (Wildfowl, 1961)
A method is described of obtaining indices to represent the relative abundance of ducks in the same month of different years and in each season as a whole. Results are based on the sample which has been used since September 1959 to produce monthly reports for observers in the National Wildfowl Count Scheme. The species investigated are Tufted Duck, Pochard, Mallard, Teal and Wigeon, and the months under consideration September to March inclusive. The period covered is from autumn 1948 to spring 1960. The Tufted Duck in Great Britain has shown an average annual increase of about 8 % and has doubled its winter population within the period under review. This rate of increase agrees well with two other estimates; one based on an unpublished study of the survival of ringed adults and of breeding success in England during the period 1949-1957, the other on the results of a survey made in the London area between 1950 and 1957. The monthly indices also agree with those obtained by a different method from a much larger sample of Wildfowl Counts. The increase in Pochard wintering in this country is equivalent to an annual rise of nearly 5% over the full twelve years. The whole of this, however, took place in the three years 1951-1954, and there has been no significant change since. Of the other species, Mallard increased steadily at an annual rate of about 2%; Wigeon showed no significant trend; and neither did Teal, although in 1959-60 an unusually large influx occurred. By comparison with previous analyses it seems that the number of Mallard in October 1959 was exceptional, and that the bulk of the Teal entered and left this country about a month earlier than usual.